Iskrivljeni odrazi
The movie was realized as a part of the project “Women and Media” of the woman's rights group B.a.B.e., Croatia. Financed by the foundation “Kvinna till Kvinna” Sweden, Dutch Embassy and Croatian Governmental Office for Cooperation with NGOs. Project Coordinator: Sanja Sarnavka, Director: Tatjana Bozic, Producers: Igor Grubic, Marko Zdravkovic. “Distorted reflections represent a sold basis fr beginning a discussion on women in the media, a correct and powerful maiden critique of the beauty industry”